A study on planar inductor coupling on a 0.25 um epitaxial CMOS process - Hizon, John Richard E. (2003)
CMOS is being considered as a potential technology in the development of personal communications system in the low GHz range. With the integration of RF systems in CMOS, planar inductors will have a crucial role on the performance of the system as a whole. In this study, the degree of coupling between two adjacent inductors is examined. The inductors were implemented using a 0.25 um epitaxial CMOS process. Coupling mechanisms considered in this study were magnetic coupling and substrate coupling. The amount of coupling is determined by measuring the S21 parameter between the inductors implemented. The effectiveness of several isolation structures reported in literature in reducing coupling between inductors was evaluated. These isolation structures include patterned ground shields and halo substrate contacts. From the measured results, it is found that a diagonal configuration improves isolation by 5 dB compared to a horizontal configuration. Furthermore, patterned ground shields are effective in improving the isolation between adjacent inductors.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Metal oxide semiconductors, Complementary; Magnetic couplings; Couplings; Electronic circuits -- Noise; Electric inductors